1989
DOI: 10.2190/m1tx-v1ej-e43l-rklf
|View full text |Cite
|
Sign up to set email alerts
|

The Beck Depression Inventory as a Screening Device for Major Depression in Renal Dialysis Patients

Abstract: Self-report measures of depressive symptoms have been frequently employed in medically ill samples despite the lack of information regarding their psychometric properties in these subjects. We have examined the agreement of the Beck Depression Inventory (BDI) with DSM-III diagnoses of depression in a sample of renal dialysis subjects (n = 99). A threshold of greater than or equal to 15 on the BDI produced optimal sensitivity (.92), negative predictive value (.99), and maximized Youden's index of validity (.72)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
195
2
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(213 citation statements)
references
References 30 publications
10
195
2
4
Order By: Relevance
“…This study showed that many dialysis patients suffer from depression, consistent with findings from studies by Hinrichsen et al (1989) and Craven et al (1988).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that many dialysis patients suffer from depression, consistent with findings from studies by Hinrichsen et al (1989) and Craven et al (1988).…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, Watnick et al (2005) found a 19% prevalence of major depression in a cohort of 62 dialysis patients from Oregon, USA. However, Craven et al (1988) found that only 8.1% met Diagnostic and Statistical Manual, Third Edition, criteria for major depression. Kimmel and colleagues reported that among outpatients who were treated with HD, approximately 25% of them were depressed, with mean BDI scores that corresponded to mild levels of depression in the general population (Cohen et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…This instrument is designed for use across a variety of age-groups, from 13 -80. In several studies Cronbach's alpha of the scale is reported to be around .85 (Ambrosini et al 1991;Craven et al 1988;Levin et al 1988;Lovibond & Lovibond, 1995;Naughton & Wiklund, 1993). (HSCL-25;Derogatis, Lipman, Rickels, Uhlenhuth, & Covi, 1974).…”
Section: The Beck Depression Inventory: Second Edition (Bdi-ii;mentioning
confidence: 99%
“…[10] Beck Depression Inventory (BDI) Depression was assessed by using the BDI, which was validated and commonly used in patients with ESRD. [11][12][13] It is reported that 85% of western dialysis patients with BDI scores of 11 or higher met DSM-IV criteria for diagnosis of major depression. [12] A BDI score of 21 has been suggested as a cut-off value for the diagnosis of depression in a Korean population.…”
Section: Quality Of Lifementioning
confidence: 99%